2021
DOI: 10.1016/j.ekir.2021.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Rare Collagenous Heterozygote Variants in Children With IgA Nephropathy

Abstract: Introduction: Childhood IgA nephropathy (cIgAN) is a primary glomerulonephritis clinically characterized by microscopic hematuria and proteinuria, the presence of which may potentially overlap with Alport syndrome. Interestingly, earlier studies suggested that familial IgAN could be linked to the chromosome 2q36 region, also the coding region for collagen type 4 alpha 3/4 (COL4A3/A4). Methods: To investigate a possible relationship or phenocopy between Alport syndrome and cIgAN, COL4A3, COL4A4, and COL4A5 exon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The presence of a glomerular disease (primary membranoproliferative GN/C3 glomerulopathy, IgA nephropathy) does not exclude AS [ 16 , 36 , 37 ]. The association between AS and immune glomerular diseases suggest that the abnormal GBM resulting from the presence of pathogenic COL4A3/A4/A5 variants may predispose to immune-mediated injury.…”
Section: What To Do When Alport Syndrome Is Strongly Suspected But a ...mentioning
confidence: 99%
“…The presence of a glomerular disease (primary membranoproliferative GN/C3 glomerulopathy, IgA nephropathy) does not exclude AS [ 16 , 36 , 37 ]. The association between AS and immune glomerular diseases suggest that the abnormal GBM resulting from the presence of pathogenic COL4A3/A4/A5 variants may predispose to immune-mediated injury.…”
Section: What To Do When Alport Syndrome Is Strongly Suspected But a ...mentioning
confidence: 99%
“…We and others reported that up to 10% of patients with diagnosis of familial FSGS have pathogenic variants in one of the COL4A genes; subsequent large studies showed that COL4A variants are the most common cause of CKD of unknown etiology in adults (6)(7)(8). Two studies also found pathogenic variants in COL4A3, COL4A4, and COL4A5 in 10-20% of patients with presumed IgA nephropathy (9,10). One approach that investigators have used to ensure accurate diagnosis of kidney disease after genetic testing is by performing reverse phenotyping after genetic testing.…”
Section: Discussionmentioning
confidence: 94%
“…Even when genetic etiology is established, there is considerable overlap between different GDs. For example it has been reported that up to 10% of classical hereditary podocytopathies (focal and segmental glomerulosclerosis) are due to pathogenic variants in COL4A genes, and pathogenic variants in these same genes have also been reported in patients with presumed IgA nephropathy (6)(7)(8)(9)(10). This reported phenotypic pleiotropy in genes associated with GD emphasizes the importance of genetic diagnosis and careful scrutiny of phenotype data after genetic diagnosis to ensure accurate disease classification (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, from clinical phenotype and renal biopsy, the coexistence of AS and IgA nephropathy is attributed to two independent causes. However, some variants in the COL4A3, COL4A4, or COL4A5 gene seem to increase the susceptibility to IgA nephropathy, which is supported by IgA deposits occasionally observed in the AS patients and the COL4A3, COL4A4, or COL4A5 gene variants reported in a minority of IgA nephropathy patients (Kamiyoshi et al, 2016;Li et al, 2020;Cambier et al, 2021). Based on the identified responsible variant, COL4A4-associated nephropathies, a sub-classification of the conditions in the two pedigrees, is strongly recommended.…”
Section: Figurementioning
confidence: 99%